Pengembangan Teknologi Informasi Digital sebagai Upaya Promosi Institusi dan Peningkatan Proses Pembelajaran - Ranti Kurniasih; Wahna Widhianingrum; Naning Kristiyana (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Human resources have a role that can determine the success of all activities in the school. Teachers are the spearhead in efforts to improve the quality of services and educational outcomes. Therefore the school seeks to prepare human resources to face the changing times. Information technology (IT) has experienced a very rapid increase in the current developments, as can be seen from the use of technological equipment whose sophistication continues to increase with the reach being achieved is increasingly expanding. In the world of education, the application of information technology is needed to support the operational activities of educational institutions such as schools. The sample for this service is 20 teachers at the Madrasah Ibtidaiyah Islamic Center Ponorogo. The activity begins with coordination with partners, planning and implementing community service activities. It is hoped that the results of this service activity with the development of digital information technology will be able to develop the learning process and help promote institutions, especially for partners, containing issues and focus of service, goals of service, methods/approaches/strategies of service research, and results of community service.